Systems Astrochemistry: A New Doctrine for Experimental Studies - Mason, Nigel J.; Hailey, Perry A.; Mifsud, Duncan V.; Urquhart, James S. (Frontiers in Astronomy and Space Sciences, 2021)
Laboratory experiments play a key role in deciphering the chemistry of the interstellar medium (ISM) and the formation of complex organic molecules (COMs) relevant to life. To date, however, most studies in experimental astrochemistry have made use of a reductionist approach to experimental design in which chemical responses to variations in a single parameter are investigated while all other parameters are held constant. Although such work does afford insight into the chemistry of the ISM, it is likely that several important points (e.g., the possible influence of experimental parameter interaction) remain ambiguous. In light of this, we propose the adoption of a new ‘systems astrochemistry’ approach for experimental studies and present the basic tenants and advantages of this approach in this perspective article. Such an approach has already been used for some time now and to great effect in the field of prebiotic chemistry, and so we anticipate that its application to experimental astrochemistry will uncover new data hitherto unknown which could aid in better linking laboratory work to observations and models.